PENGARUH PELAYANAN, HARGA DAN PROMOSI TERHADAP LOYALITAS PELANGGAN PADA PENGGUNA GO-JEK DI DAERAH ISTIMEWA YOGYAKARTA - Sarjita Sarjita (Sekolah Tinggi Ilmu Bisnis Kumala Nusa Yogyakarta, 2018)
The purpose of this study is to analyze the variable quality of service, price and promotion of customer loyalty to Go-Jek users in Yogyakarta Special Region. Data collection in this study using questionnaires, which are distributed to Go-Jek users in Yogyakarta Special Region. Sampling technique used is non probability sampling, with one method is purposive sampling. The number of respondents in this study as many as 100 people. The data obtained were then analyzed using SPSS 20. Based on the research result, it is found that service (X1), price (X2) and promotion (X3) have positive and significant influence on customer loyalty (Y) to Go-Jek users in Yogyakarta Special Region